Analysis of The Influence of Online Purchase Decisions, Digital Perceive Value of Quality and Digital Viral Marketing on Consumer Satisfaction of Skincare Products - Fitri, Sari; Wisnu Wardana, Yoga Fortuna; Mustafa, Fahrina; Sari, Efti Novita; Arief, Ilham (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to determine whether consumer happiness is influenced by product quality, viral marketing, and purchase decisions. The population under study in this study consists of customers who use skincare products. The sample is a portion of the population's size and makeup. Non-probability sampling strategies were employed in this study. A total of 100 respondents made up the sample for this investigation. Researchers employed questionnaires as a means of gathering information from respondents in order to compile the necessary data. This study's questionnaire approach makes use of a Likert scale. This study falls under the category of explanatory research, which uses hypothesis testing to understand cause-and-effect correlations between variables. With the aid of SPSS software, researchers in this study used the path analysis method to evaluate the data. Based on the information that researchers have acquired and analyzed throughout the testing stage, the following conclusions may be drawn: Purchase decisions are directly impacted by the quality of the product. Purchase decisions are directly impacted by viral marketing. Purchase decisions are influenced by viral marketing and product quality at the same time. Customer happiness is directly influenced by the quality of the product. Customer happiness is directly impacted by viral marketing. Customer happiness is directly impacted by purchase decisions. Customer satisfaction is influenced by purchase decisions, viral marketing, and product quality all at once. Product quality influences consumer satisfaction through purchasing decisions. Viral marketing influences consumer satisfaction through purchasing decisions.